Peran Psikologi dalam Pendidikan Islam: Landasan Teoretis dan Implikasinya terhadap Proses Pembelajaran - Yaman, Nur; Rohimah, Siti (TSAQOFAH, 2026)
Psychology plays an important role in Islamic education as a foundation for understanding students holistically from cognitive, affective, and spiritual dimensions, so that the learning process is not only oriented toward knowledge transfer but also toward personality development. This study aimed to examine the role of psychology in Islamic education from a theoretical perspective and its implications for the learning process. A library research method was employed by analyzing various scientific journals published over the last ten years that are relevant to the theme of Islamic educational psychology. The findings show that the integration of Islamic values and modern psychological theories can foster a learning process that is holistic, humanistic, and oriented toward character formation. Islamic educational psychology contributes to curriculum development, the enhancement of learning motivation, and the development of students’ emotional and spiritual intelligence. Thus, an Islamic psychological approach constitutes an essential foundation for realizing Islamic education that is not only oriented toward knowledge acquisition, but also toward moral development and the personality balance of students.